Isoproterenol-induced FKBP12.6/12 downregulation is modulated by ETA and ETB receptors and reversed by argirhein, a derivative of rhein - Zhang Guo-lin; Dai De-zai; Xi Tao; Cong Xiao-dong; Zhang Yun; Dai Yin (Acta Pharmacologica Sinica, 2016)
Aim: To investigate which endothelin receptors mediated isoproterenol (ISO)-induced downregulation of FKBP12.6/12 in cardiomyocytes and study whether argirhein, a novel compound containing rhein and L-arginine that has anti-inflammatory activity, could reverse the downregulation of FKBP12.6/12 induced by ISO. Methods: Neonatal rat cardiomyocytes were incubated with ISO to downregulate FKBP12.6/12. Then the cells were treated with a selective ETA blocker (PD156707) and a ETB blocker (IRL1038), a dual ETA/ETB antagonist (CPU0213), and argirhein, respectively. FKBP12.6/12 expression was assayed by RT-PCR, Western blot, and immunocytochemistry. Results: The expression of FKBP12.6 mRNA was reduced by 37.7% (P